Pengaruh Faktor-Faktor Motivasi terhadap Kinerja Pegawai Dinas Bina Marga dan Sumber Daya Air Kota Bogor - Handayani, Prima Dessy; Hutagaol, M.Parulian; Affandi, M. Joko (Universitas Brawijaya, Indonesia, 2015)
Highways and Water Resources Department is one part of the local governmentorganizations in Bogor in which has the task to formulate technical policy and providepublic services in the field of community development and water resources. This courserequires a highly performance to be able implementing the tasks well. However, theorganization's efforts to improve productivity experience have a variety obstacle. One of thebiggest obstacles is declining of the employee's performance caused by decreasing of employeemotivation. The aim of this study is assessing the motivation factors of the mostinfluence on employee performance. Data collection techniques of this study used observation,interview and questionnaire with semantic scale techniques. Data analysis was performedby multiple linear regression analysis method. The analysis results of the influence ofmotivational factors on the performance showed that there is extrinsic work motivationfactors on employee performance than intrinsic work motivation factors. Extrinsic motivationfactor has the most influence to the employees performance of Highways and WaterResources Department, the policy and administration, and working conditions in Bogor.